Internet of Things, Smart Spaces, and Next Generation Networks and Systems : 15th International Conference, NEW2AN 2015, and 8th Conference, ruSMART 2015, St. Petersburg, Russia, August 26-28, 2015, Proceedings - Balandin, Sergey; Andreev, Sergey; Koucheryavy, Yevgeni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the joint refereed proceedings of the 15th International Conference on Next Generation Wired/Wireless Advanced Networks and Systems, NEW2AN 2015, and the 8th Conference on Internet of Things and Smart Spaces, ruSMART 2015, held in St. Petersburg, Russia, in August 2015. The 74 revised full papers were carefully reviewed and selected from numerous submissions. The 15 papers selected for ruSMART are organized in topical sections on IoT infrastructure, IoT platforms, smart spaces and IoT cases, and smart services and solutions. The 59 papers from NEW2AN deal with the following topics: streaming, video, and TCP applications, mobile "ad hoc" networks, security, and clouds, sensor networks and IoT, cellular systems, novel systems and techniques, business and services, signals and circuits, optical and satellite systems, and advanced materials and their properties.
Keywords: Computer Communication Networks; Computer system performance; Information Systems; Telecommunication; Computer Communication Networks; System Performance and Evaluation; Management of Computing and Information Systems; Communications Engineering, Networks